XI Brazilian Power Electronics Conference 2011
DOI: 10.1109/cobep.2011.6085242
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the photometrical impacts of several current waveforms on power white LEDs

Abstract: Since light-emitting diodes (LEDs) are a rising lighting technology, a great amount of research is currently being focused on driving techniques for these current-fed semiconductor devices. For realizing efficient current drivers, power electronics is usually employed. This work focuses on studying the impacts that several high and low frequency current waveforms commonly found on power electronic drivers may have on the photometrical and colorimetrical performance of the LEDs themselves. Empirical evidence ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
0
14
0
5
Order By: Relevance
“…A reference value for maximum current ripple that has been recently established is 50% peak to peak in relation to the average current. Below this limit, minimal to no discernible alterations have been measured in the LEDs' light output [16]- [19], and the generated flicker remains below the threshold that could cause human health issues. It has been demonstrated that for 50% LED current ripple, the flicker remains below 25% [20].…”
Section: Leds Are Limited By Their Driversmentioning
confidence: 99%
“…A reference value for maximum current ripple that has been recently established is 50% peak to peak in relation to the average current. Below this limit, minimal to no discernible alterations have been measured in the LEDs' light output [16]- [19], and the generated flicker remains below the threshold that could cause human health issues. It has been demonstrated that for 50% LED current ripple, the flicker remains below 25% [20].…”
Section: Leds Are Limited By Their Driversmentioning
confidence: 99%
“…Por isso, o conversor Buck-Boost pode ser aplicado para a correção do fator de potência e ainda alimentar os LEDs a partir da rede (operando como abaixador de tensão) ou da bateria (operando como elevador de tensão). Para LED, estudos têm mostrado que sua alimentação com corrente constante propicia maior eficiência luminosa [21]- [23]. Da mesma forma, um dos métodos de carga de bateria é alimentá-la com corrente constante [24].…”
Section: Sistema Propostounclassified
“…Para la reducción de la huella de carbono y el costo en iluminación se han comenzado a desarrollar opciones mediante unidades inteligentes de control de iluminación de LED, como en el tráfico vehicular ajustando la intensidad de la iluminación de acuerdo el volumen vehicular [8]. La alta eficiencia luminosa, el alto índice de reproducción cromática o CRI por sus siglas en inglés, su larga vida útil y emisión de luz blanca, la hacen una buena candidata para aplicaciones de iluminación en interiores y muy adecuada para la iluminación pública [5]. La iluminación en exteriores juega un papel importante para el funcionamiento y seguridad en los centros urbanos.…”
Section: Introductionunclassified